The Influence of Beauty Vlogger Endorsements on Purchase Interest (Survey of Wardah Cosmetics Enthusiasts Who Are Influenced by Tasya Farasya's Vlog Video in East Semper Village, North Jakarta - Gulo, Helena Haltini; Sahab, Nur Dina; Irawan, 3Pristanto Ria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research examines the influence endorsement of beauty vloggers on interest in purchasing Wardah cosmetics, with a focus on fans who were influenced by Tasya Farasya's vlog video in Semper Timur Subdistrict, North Jakarta. The main aim of the research is to analyze the extent to which content created by beauty vloggers influences consumer purchasing decisions in the cosmetics industry. The research method used was a survey, with respondents selected from Wardah cosmetics fans who watched Tasya Farasya's vlog video. Data was collected through questionnaires and analyzed using a purposive sampling method with 30 respondents. The research results show that there is a positive correlation between endorsement beauty vlogger and interest in purchasing Wardah cosmetics. Factors such as vlogger credibility, content quality, and relevance of the product reviewed were found to play a significant role in influencing consumer purchasing decisions. This research provides valuable insights for the cosmetics and digital marketing industry, especially in utilizing the influence of beauty vloggers as an effective marketing strategy.